2004
DOI: 10.1590/s1517-83822004000200002
|View full text |Cite
|
Sign up to set email alerts
|

Production of aflatoxins by Aspergillus flavus and of fumonisins by Fusarium species isolated from Brazilian sorghum

Abstract: Fifty-nine Aspergillus flavus and 35Fusarium verticillioides strains, isolated from freshly harvested (10) and stored (130) Brazilian sorghum samples, were tested regarding their ability to produce aflatoxins (coconut milk agar) and fumonisins (rice culture), respectively. Aflatoxins B1 and B2 were detected by TLC, and fumonisins B1 and B2 were analyzed by HPLC. Thirty-eight (64.4%) A. flavus strains produced detectable levels of aflatoxins at concentrations ranging from 12.00 to 3282.50 µg/kg (AFB1 + AFB2), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…A large portion of industrial dairy farms use sorghum silage as a main source of energy in their feeding systems. Sorghum is a worldwide grass originating from the African and Asian continents and has been considered as one of the AFB 1 sources (Da Silva, Dilkin, Fonseca, & Correa, 2004). Regarding the above environmental conditions, it is well known that temperatures between 27°C and 38°C and relative humidity of 85% (corresponding to 18% grain moisture) are optimum for growth of Aspergillus (Grybauskas, Thomison, & Cassel, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…A large portion of industrial dairy farms use sorghum silage as a main source of energy in their feeding systems. Sorghum is a worldwide grass originating from the African and Asian continents and has been considered as one of the AFB 1 sources (Da Silva, Dilkin, Fonseca, & Correa, 2004). Regarding the above environmental conditions, it is well known that temperatures between 27°C and 38°C and relative humidity of 85% (corresponding to 18% grain moisture) are optimum for growth of Aspergillus (Grybauskas, Thomison, & Cassel, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The production of fumonisins by different strains of F. proliferatum varies widely. Some studies have shown that only low or even no fumonisin production (Tseng et al 1995;Da silva et al 2004), while other study has shown that, F. verticillioides can produce high levels of fumonisins (Nelson et al 1992). The natural occurrence of fumonisin B1 in Indian sorghum, where the contamination levels ranging from 0.01-5.0 mg/kg and 0.15-0.51 mg/kg has been reported (Shetty and Bhat 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The natural occurrence of fumonisin B1 in Indian sorghum, where the contamination levels ranging from 0.01-5.0 mg/kg and 0.15-0.51 mg/kg has been reported (Shetty and Bhat 1997). (Da silva et al 2004) reported that production of fumonisins by Fusarium species in Brazilian sorghum. Fumonisins have also been detected at lower levels in sorghum (Shetty and Bhat, 1997;Leslie and Marasas, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Occurrence of mycotoxin producing fungal species in grains and grain based food has been reported in many countries with a high frequency of Aspergillus and Fusarium taxa (Da Silva et al 2000;Kumar et al 2008). Mycotoxigenic seed-borne Aspergillus and Fusarium strains have been isolated from both freshly harvested and stored Brazilian sorghum (Da Silva et al 2004). Recovery of several other mycotoxigenic fungi from sorghum grains have been frequently documented (Thakur et al 2006;Makun et al 2009).…”
Section: Introductionmentioning
confidence: 99%